(untitled) (ModaPalavra e-periódico, 2019)
This article seeks to describe and analyze the fashion digital influencers, famous characters on social media that uses their influence on people to promote fashion items. We will oppose the idea of fashion sense as a personal thing and talk about it as a coercive process imposed by the society we live in. We will highlight how the computer-mediated communication changes the way fashion itemsare sold for the ones that follow those Instagram celebrities and how fashion brands are using them to advertise. Despite using a well known way to advertise –photography –we cannot deny that the consumers see those in a different way, as influencers are not famous people (models, actresses or singers) and the publicity is done on social media (not a fashion magazine). Some of the consumers don’t even notice that they are advertising those things. We associate this phenomenon to the theory of “micro-celebrity” (BRAGA, 2008), to comprehend the relation between digital influencers and fashion production chain.